Model ekonomiczno-matematyczny branży przemysłowej, cz. II - Bogucki, Zdzisław (Wydział Prawa i Administracji UAM, 1969)
The paper, the second part of a large work, presents an application of computing techniques to managing and controlling the process of machine industry development. A mathematical model of the economics of industry has been designed which makes possible to trace out the consequences of various feasible decisions adopted for making and developing the branch of industry. It is the feed-back-type model assuming close collaboration between "man and computer". The methods of computing the rate of production and the productivity as well as productivity requirements have been described in this paper. It concerns a period of three successive years in several sections of accuracy for 1 m variations. The pattern of the tables has been carried out in the form of multidimensional matrixes which are linked by applying the rules of matrix element calculus. The results of computing i.e. the requirements of the productivity increase are balanced with the supply possibilities of the requirements concerned. The balancing will be presented in the third part of the work to be published in the next issue of this journal.
Mathematical and Economic Model of a Branch of Industry